Species richness and functional types: their relation in sacred-fir forests of Mount Tlaloc, Mexico State - Sánchez-Sánchez, Cristóbal; Paz-Pellat, Fernando; Hernández-de la Rosa, Patricia; Velázquez-Rodríguez, Alma; Vibrans, Heike; Vargas-Hernández, Jesús; Valdez-Hernández, Juan Ignacio; Valdez-Lazalde, J. René (Instituto de Ecología, A.C., 2021)
The diversity of vascular plants is related to the productivity and resilience of forests, and therefore, the development of indicators for itscharacterization is fundamental. The richness of vascular species (S) has been shown to be a good indicator of other biological groups diversity.It has also been proposed that the type of functional plant richness (Sg) significantly correlates with the species richness and, therefore,can be used as a substitute indicator. This paper analyzes the relationship between richness and sampling area (A), with theoreticaland empirical data, to propose a generalized theoretical framework of the relations between the parameters of the curves: S-A, Sg-A andS-Sg. The power and logarithmic models of functional vascular plant types and richness-area accumulation curves are assessed, characterizingfunctional types through a classification based on 36 functional attributes, in 15 sampling sites of 1000 m2 in the sacred-fir forestsof Mount Tlaloc, State of Mexico. Results show richness estimates comparable with the direct measurements, obtained by using onlyone type of richness to estimate the other. This can greatly simplify the implementation of diversity indicators in vascular plant surveys.